(untitled) (Academia Science Repository, 2023)
In the past decade there has been a surge of research interest in morphological awareness (MA), which refers to an individual’s ability to decode the morphemic structure of words and further analyze them. This review gives conceptual insights into MA from linguistic perspectives and provides some implications for English language teaching based on empirical research findings. Recent research into MA suggests that there is a significant rate of achievement among students who are exposed to strategies for not only understanding the meanings of words but also recognizing different morphological forms of the same word in reading texts, as opposed to students who are not exposed to such strategies. Indeed, a large number of studies conducted have established that MA is a critical factor in enabling comprehension and ensuring that students have a clearer understanding of vocabulary. In addition, it has emerged that for many educators, an emphasis on a clear understanding of such aspects as prefixes,suffixes, and roots determines the success rate in teaching vocabulary. Therefore, language teachers can engage in teaching MA in the classroom as part of explicit language instruction by adopting some instructional strategies that can be adjusted to suit each age group.